2012
DOI: 10.1007/s00520-012-1581-x
|View full text |Cite
|
Sign up to set email alerts
|

In-advance end-of-life discussions and the quality of inpatient end-of-life care: a pilot study in bereaved primary caregivers of advanced cancer patients

Abstract: Advanced cancer patients may receive higher quality of inpatient EOL care if they had in-advance EOL discussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
2
23
0
1
Order By: Relevance
“…5 Conversely, families have reported a higher quality of care when advance care planning occurs, especially earlier in the disease process. 6 Unfortunately, both families and clinicians believe that ACD often happen too late in the course of a patient's illness. 7,8 Recognizing the need to improve EOL communication, several palliative care experts have developed consensus recommendations to assist clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…5 Conversely, families have reported a higher quality of care when advance care planning occurs, especially earlier in the disease process. 6 Unfortunately, both families and clinicians believe that ACD often happen too late in the course of a patient's illness. 7,8 Recognizing the need to improve EOL communication, several palliative care experts have developed consensus recommendations to assist clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Patients in this situation who do not have advance directives often receive default invasive treatments, such as mechanical ventilation, which may not align with their goals of care [ 3 ]. Advance care planning (ACP) includes establishing advance directives and often involves discussions between the patient, family members, and outpatient clinicians [ 4 ]. Although most patients are open to discussing end-of-life issues, few have had such conversations with a doctor [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limited role of chemotherapy in the advanced stage, high prevalence of misunderstanding the goal of treatment and disease prognosis was reported in advance cancer patients . Advanced cancer patients with inappropriate understanding of their illness are likely to choose aggressive care at end of life (EOL) . A previous study showed that approximately 32–69% of patients have inappropriate understanding of the effectiveness of palliative chemotherapy .…”
Section: Introductionmentioning
confidence: 99%